Evaluation of the effectiveness of two structures for coral gardens of the species Acropora cervicornis (Scleractinia: Acroporidae) in Portobelo National Park. - Bernal, Luis Enrique; Gonzales, Yessenia del Carmen; Medina, Beatriz del Carmen; Gómez, René Ricardo (Revista de Biología Tropical, 2023)
Introduction: In Panama and the world, for several years, reefs have been threatened by actions such as coastal development, sedimentation, and contamination by terrestrial entities, which are the most frequent, giving rise to the implementation of restoration methodologies. Objective: To compare the efficiency of two coral garden structures in the growth of the species Acropora cervicornis in Huertas Bay, Portobelo National Park, Colon Panama. Methods: Two fixed-type structures were placed, using PVC together with hydraulic concrete bases, and two clothesline-type structures, using PVC and nylon thread. The coral fragments that were placed in the structures came from Bahía Huertas and Buenaventura Island. The growth of the corals was determined using the linear growth and tissue extension measurement method. Results: A total of 80 coral fragments were planted, representing an estimated extension of 9.71 m of coral in Huertas Bay. After nine months of study, a total of 15.3 m of totally new coral (1 525.6 cm) was estimated, where only 4.6 % belonged to the fragments of the fixe-type structure, while 95.4 % belonged to the clothesline-type structure. Conclusions: The clothesline-type structure was the most efficient and viable within the study, with better survival and growth rate compared to the fixed type structure, where it did present a mortality of 45 %.